Optimization of ammonia production from urea in continuous process using ASPEN Plus and computational fluid dynamics study of the reactor used for hydrolysis process - Sahu, J.N.; Chava, V.S.R.K.; Hussain, S.; Patwardhan, A.V.; Meikap, B.C. (Elsevier, 2010)
The present study addresses the methods and means to safely produce relatively small amounts (i.e., up to 50 kg/h) of ammonia. The optimization and simulation study conducted for continuous process and effect of operation conditions like reaction temperature, initial feed concentration and pressure on ammonia production carried out using ASPEN Plus. Also, a computational fluid dynamics (CFD) model was proposed to simulate the hydrolysis of urea for synthesis of ammonia. A series of parametric studies to investigate flow rates, thermal boundary conditions and reactor geometry was performed for hydrolysis of urea and the optimized operating conditions and reactor geometry were obtained. Detailed three-dimensional flow, heat and chemistry simulations of ammonia, carbon dioxide and ammonium carbamate. The study demonstrates that simulation is a useful tool for diagnosing hydrolysis reactor mixing pathologies and for identifying practical countermeasures that could improve process performance. (C) 2010 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.